PSYCHOLOGICAL COUNSELING AND SOCIAL SUPPORT FOR INDIVIDUALS WITH AGGRESSIVE AND VICTIMIZING BEHAVIOR - Ivanov, Krasimir; Petkova, Pavlina (E-Journal VFU, 2025)
The article is dedicated to a major socially significant issue - the problem of aggressive, respectively victim behavior. The main models for professional psychological counseling and social assistance are presented.
Keywords: aggression; victim behavior; psychological counseling; social support